Packet scheduling algorithms for long term evolution - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan (IIUM Press, 2011)
Long Term Evolution (LTE). which is now referred to as 3.9G, is the latest commercially available Third Generation Partnership Project (3GPP) standard. It was designed to meet users' demand for high speed multimedia communication. It uses 011hogonal Frequency Division multiple Access (OFDMA) for downlink transmission. OFDMA is a multi-carrier access technology that divides the available wide bandwidth into multiple cqually spaced sub-carriers [I]. The minimum transmission unit that is available to be shared among the downlink LTE users is known as a Resourcc Block (RB). An RB is made up of 12 subcarriers (180 kHz total bandwidth) of I ms duration [2]. The LTE employs a simplified Evolved Universal Terrestrial Radio Access Network (E-CTRAN) architecture that only consists of base stations called enhanced node Bs (eNBs).